Toleransi Beragama sebagai Penghormatan pada Pluralitas Quidditas Manusia: Telaah Pemikiran Nicholas dari Cusa - Stau, Januarius Martin (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2024)
This article aims to explore Nicholas of Cusa’s views on religious tolerance based on a reading of his work De Pace Fidei. There are some of his ideas that might be useful in the context of religious tolerance. A dialogue among various religious beliefs is one way to find the common ground. For Nicholas, ratio is the way to unify diverse religions, because by nature humans have a desire to know truth, wisdom and God. He believes that the power of ratio is at the same time a belief in the universal grace of God. Nicholas concludes that the purpose of interreligious dialogue is to affirm “uno religio in rituum varietate.” People worship “the same God” in various rites, and different rites are tolerated because through them humans are active and creative in their ways to arrive at the Divine. The basis of Nicholas’ religious tolerance lies in respect to the plurality of unique individuals. He tolerates the plurality of religious rites to a certain degree insofar as they adhere to certain universal principles and live in harmony as expressions of belief in the “One” and bases such plurality on the ontological plurality of human beings.